In vitro study the effect of laser photon-induced photoacoustic streaming on the enterococcus faecalis biofilm in complicated root canal system - Ibrahim, Ghufran I.; Jawad , Hussein A. (Iraqi Journal of Laser, 2026)
gallium garnet (Er, Cr: YSGG) laser using photon-induced photoacoustic streaming (PIPS) in the agitation of irrigation fluids in the complicated root system that infected with Enterococcus faecalis (E. faecalis). Methods: The mesial roots of 90 recently extracted first and second lower human molars were separated, injected with Enterococcus faecalis suspension (except for the negative control group samples), and cultivated for thirty days. The samples were divided into five groups (n=15), first group acted as a positive control (inoculated untreated) (G1), syringe irrigation groups were irrigated with 5.25% sodium hypochlorite (NaOCl) (G2) and 2% chlorohexidine gluconate (CHX) (G4), laser groups were irrigated by 5.25% NaOCl (G3) and 2% CHX (G5) with Er, Cr: YSGG laser activation at 700 µs, 5 Hz, (0.25, 0.5, 0.75, 1, and 1.25) W. AFM, or atomic force microscope, was employed as a novel technique to obtain data in the isthmus region. A scanning electron microscope (SEM) was also used in the study to confirm the results obtained from an atomic force microscope parameter. Statistical Package for Social Sciences (SPSS) software was used to collect and analyze data, and the study groups' means were compared using analysis of variance (ANOVA). Results: After the results were statistically analyzed, the laser group with 2% chlorohexidine gluconate and 5.25% sodium hypochlorite showed a significant decrease in surface roughness than the syringe irrigation and the positive control groups (p